Measuring. Monitoring. Management. Control - B.V. Tsypin; S.P. Prokopchuk (Измерение, мониторинг, управление, контроль)
Background. The object of the study is technological testing of complex technical products. The subject of the study is the assessment of measurement results during technological testing. The purpose of the work is to present methods and criteria for assessing inspection results. Materials and methods. The basic mathematical relationships, recommendations for the organization and procedure of testing and for assessing measurement results are given. The theoretical material is illustrated by an example of analyzing the results of a technological inspection of a railway radio station. Results. The material in the article allows us to objectively assess the quality of the test based on the criteria of stability, convergence and reproducibility of measurement results, bias of results and its linearity. Conclusions. The presented materials allow us to assess the acceptability of the measurement process based on the recommendations of state standards of the Russian Federation.